A Fragility, which Connects: Music as a Social Encounter - Fusi, Marco (2023)
The following is a discussion between Charlie Sdraulig, Marco Fusi, Winnie Huang, and Gwen Rouger made during April of 2023. Charlie Sdraulig’s work one to one is an intimately staged sequence of three performances, each for one performer and one audience member at a time, comprising: one to one (2018-19) for vocalising violinist and audient for Marco Fusi, tend (2019) for gesturing, vocalising performer and audient for Winnie Huang, and enfold (2019-20) for pianist on an amplified, old upright, and audient for Gwen Rouger. The discussion relates the project’s origins, collaborative workshops, interactive performance experiences, and more.
FRIS
Editorial review
Keywords: Sdraulig, Charlie; HIPEX: Historical Performance Practices of Experimental Music; Performance art